Older Adults Vs Middle-Aged Adults: Heel Velocity (International Journal of Innovative Research in Computer Science & Technology, 2020)
The objective of the present study was to  evaluate heel contact velocity of middle-age adults and  older adults. Ten adults (5 middle age adults and 5 older  adults) were recruited from a local community. They were  all physically healthy and not injured in the last 6 months.  Their heel position data were collected during subsequent  5-minute walking on a straight track (15m long). The  results indicated that heel contact velocity of middle-age  adults were faster than that of older adults during their  natural gait. The study concluded that middle-age adults’  heel contact velocity could be faster suggesting that their  slip propensity could be higher compared to older adults  while walking on a leveled floor.
Keywords: HCV; Middle age; Older; Foot force